2010
DOI: 10.1199/tab.0124
|View full text |Cite
|
Sign up to set email alerts
|

From Perception to Activation: The Molecular-Genetic and Biochemical Landscape of Disease Resistance Signaling in Plants

Abstract: More than 60 years ago, H.H. Flor proposed the "Gene-for-Gene" hypothesis, which described the genetic relationship between host plants and pathogens. In the decades that followed Flor's seminal work, our understanding of the plant-pathogen interaction has evolved into a sophisticated model, detailing the molecular genetic and biochemical processes that control host-range, disease resistance signaling and susceptibility. The interaction between plants and microbes is an intimate exchange of signals that has ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 165 publications
0
28
0
1
Order By: Relevance
“…35 The outcome of the viral infection is due to the compatibility of the interactions between plant pathogen sensors and the pathogen molecules. 6 However, how the host can affect the physiochemical properties of the virions is not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…35 The outcome of the viral infection is due to the compatibility of the interactions between plant pathogen sensors and the pathogen molecules. 6 However, how the host can affect the physiochemical properties of the virions is not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of characterized plant R proteins belong to the nucleotide binding-leucine-rich repeat (NB-LRR) class, which can be subdivided into two categories depending on whether the N terminus contains a toll-interleukin-1 receptor (TIR) domain or a coiled-coil (CC) domain (Collier and Moffett, 2009;Lukasik and Takken, 2009;Knepper and Day, 2010). Genetic analyses initially suggested that CC-type R proteins generally signal defenses via NDR1 (for Nonspecific Disease Resistance 1, At3g20600), whereas TIR-type NB-LRR proteins usually use EDS1 (Aarts et al, 1998).…”
Section: Signaling/regulatory Modulators Of Induced Sa Accumulation: mentioning
confidence: 99%
“…To accomplish this, the activation of plant resistance signaling requires the utilization of numerous preformed defense responses, systemic and cell-to-cell signaling, and, in many cases, the initiation of gene-for-gene resistance (Knepper and Day, 2010). While examples of the activation and regulation of parallel processes have been described (van Wees et al, 2000), there are numerous instances in which bifurcation exists .…”
mentioning
confidence: 99%